Galectin-9 treatment is cytotoxic for B cell lymphoma by disrupting autophagy - Koll, Lisanne; Lourens, Harm Jan; Marsman, Glenn; de Haan, Stan; Niki, Toshiro; Huls, Gerwin A.; Bremer, Edwin; Wiersma, Valerie R. (Frontiers in Pharmacology, 2025)
IntroductionThe main cause of death for patients with non-Hodgkin lymphoma (NHL) remains therapy resistant relapses. Chemoresistance is commonly associated with apoptosis defects and upregulated autophagy. Therefore, novel therapeutic options that do not rely on apoptosis and target autophagy would be of interest to treat NHL. An agent that may fulfill these requirements is the glycan-binding protein Galectin-9 (Gal-9).MethodsA panel of B cell lymphoma NHL cell lines, including diffuse large B cell lymphoma (DLBCL), mantle cell lymphoma (MCL), Burkitt’s lymphoma (BL), and (chemoresistant) follicular lymphoma (FL), were treated with Gal-9 after which cell counts and cell viability were determined. Basal mRNA and protein expression levels were respectively determined by RTqPCR and western blot. The impact of Gal-9 treatment on the autophagy pathway was determined using lysotracker, Cyto-ID and western blot (targeting LAMP2, p62, LC3B-I/LC3B-II).ResultsTreatment with Gal-9 reduced total cell counts and cell viability of various DLBCL, MCL, BL and FL cell lines. Gal-9-induced cell death was associated with the inhibition of autophagy, as demonstrated by the accumulation of LC3B-II and p62. In addition, Gal-9-sensitive cells expressed lower basal protein levels of LC3B-I as compared to cells that responded less to this lectin. Furthermore, Gal-9 was cytotoxic for chemoresistant Sc-1 cells (Sc-1-RES), which were even more sensitive toward Gal-9 treatment than the parental cells (Sc-1-PAR).ConclusionGal-9 is a potent inducer of B cell lymphoma cell dead by inhibiting the proper execution of autophagy.